Maximum Likelihood Estimation and Non-Linear Least Squares Fitting Implementation in FPGA Devices for High Resolution Hodoscopy - Blasco, Jose M.; Sanchis, Enrique; Gonzalez, Vicente; Martin, Jose D.; Egea, Francisco J.; Barrientos, Diego; Granero, Domingo; Sanchis-Sanchez, Enrique (IEEE transactions on nuclear science, 2013)
This work compares two possible solutions to achieve a high resolution in a hodoscope based on Plastic Scintillating Fibers (PSF) by obtaining the point of maximum interaction of the radioactive beam with the detector. The two fitting algorithms are the Maximum Likelihood Estimation and a non-linear least-squares fitting with the Levenberg-Marquardt Algorithm. Both approaches have been tested, compared and implemented in Field Programmable Gate Array (FPGA) devices.